2017
DOI: 10.1177/2041731417702531
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of dental stem cells

Abstract: Stem cell biology has become an important field in regenerative medicine and tissue engineering therapy since the discovery and characterization of mesenchymal stem cells. Stem cell populations have also been isolated from human dental tissues, including dental pulp stem cells, stem cells from human exfoliated deciduous teeth, stem cells from apical papilla, dental follicle progenitor cells, and periodontal ligament stem cells. Dental stem cells are relatively easily obtainable and exhibit high plasticity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
156
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(163 citation statements)
references
References 161 publications
(223 reference statements)
0
156
0
7
Order By: Relevance
“…In corneal production A study put forward its findings that a tissue engineered DPSC sheet when transplanted on the corneal bed and further on it was converted with the help of de-epithelialized human amniotic membrane, the histological analysis at three months postoperative phase confirmed that a healthy uniform corneal epithelium was formed. Thus, it was concluded that tissue engineered DPSC sheet was successful for the reconstruction of corneal epithelium (18,45).…”
Section: Differentiation To Hepatocytementioning
confidence: 99%
“…In corneal production A study put forward its findings that a tissue engineered DPSC sheet when transplanted on the corneal bed and further on it was converted with the help of de-epithelialized human amniotic membrane, the histological analysis at three months postoperative phase confirmed that a healthy uniform corneal epithelium was formed. Thus, it was concluded that tissue engineered DPSC sheet was successful for the reconstruction of corneal epithelium (18,45).…”
Section: Differentiation To Hepatocytementioning
confidence: 99%
“…Dental stem cells (DSCs) are self-renewable teeth cells, which help maintain or develop oral tissues 6 . In the literature, there are various types of dental adult stem cells, such as dental pulp stem cells (DPSCs), stem cells from human exfoliated deciduous teeth (SHEDs), periodontal ligament stem cells or stem cells of the developing root apical papilla (SCAPs), dental follicle stem cells (DFSCs), and dental MSCs (DMSCs) 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…24,26 Dental/oral stem cells Mesenchymal stem cells can be isolated from several dental locations (pulp, exfoliated primary deciduous teeth, apical papilla, dental follicule, periodontal ligament) as well as from some other oral tissues (gingiva, oral mucosa, craniofacial bone). 27 Dental stem cells (DSCs) are derived from neural crest post natal stem cell populations with MSC-like characteristics. Compared to BM-MSCs, the DMSCs appear to be more related to odontogenic than osteogenic development.…”
Section: 25mentioning
confidence: 99%